PENGARUH PERSEPSI HARGA DAN FOMO TERHADAP KEPUTUSAN PEMBELIAN PRODUK COKLAT DUBAI - Manalu, Anggriani Br; Tyra, Maria Josephine (Catholic University Musi Charitas, 2026)
Purpose: This study aims to examine the influence of price perception and fear of missing out on purchasing decisions for Dubai Chocolate products, considering the growing phenomenon of viral consumption driven by both rational and psychological factors. Design Methodology Approach: A quantitative survey was conducted among individuals who had purchased Dubai Chocolate products. A total of 100 respondents were selected using purposive sampling. Data were analyzed using multiple linear regression to assess the effect of price perception and FoMO on purchasing decisions. Findings: The results indicate that both price perception and FoMO have a positive and significant effect on purchasing decisions. Price perception demonstrates a stronger influence compared to FoMO, suggesting that consumers still rely on value evaluation despite exposure to social pressure. Practical Implications: The findings suggest that businesses should maintain a balance between pricing strategies and psychological triggers in marketing. Competitive pricing combined with the ability to create social desirability can enhance purchasing decisions, particularly for products positioned within viral trends. Originality Value: This study provides empirical evidence on the simultaneous role of rational evaluation and psychological pressure in shaping purchasing decisions within viral product contexts, offering a more integrated perspective on consumer behavior.